The great wall of China in history and legend - Luo, Zhewen; Luo, Zhao (Beijing, China : Foreign Languages Press, 1986)
To most foreigners the words "the Great Wall" and "China" are nearly synonymous, for their geography textbooks have all taught them about one of the great wonders of the world. For the Chinese its somewhat the same, for a Chinese saying goes: "You won't be considered a great man if you have not been to the Great Wall."
A Brief History of the Great Wall -- Why Was the Great Wall Built? -- The Functions, Military Layout and Structure of the Great Wall -- How the Great Wall Was Built -- Some Well-known Remains of the Great Wall -- Appendices -- Legend of the Great Wall -- Chronological Table of Chinese History -- Genealogical Table of the Qin, Han and Ming Dynasties -- Units of Measure of Each Dynasty -- Bibliography of Books on the Great Wall.
Includes bibliographical references.
Keywords: GREAT WALL OF CHINA (CHINA)